Timely accessibility to healthcare resources and heatwave-related mortality in 7 major cities of South Korea: a two-stage approach with principal component analysisResearch in context - Jungsil Lee; Jieun Min; Whanhee Lee; Kyongmin Sun; Won Chul Cha; Chaerin Park; Cinoo Kang; Juyeon Yang; Dohoon Kwon; Youngrin Kwag; Jongmin Oh; Jae-Hong Ryoo; et al. (Elsevier, 2024)
Summary: Background: Due to the ongoing effects of climate change, the incidence of heatwave-related mortality is rising globally. Improved allocation and utilization of healthcare resources could help alleviate this issue. This study aimed to identify healthcare resource factors associated with heatwave-related mortality in seven major cities of South Korea. Methods: We analyzed daily time-series data on mean temperature and all-cause mortality from 2011 to 2019. Using principal component analysis (PCA), we clustered district-level healthcare resource indicators into three principal components (PCs). To estimate district-specific heatwave-mortality risk, we used a distributed lag model with a quasi-Poisson distribution. Furthermore, a meta-regression was performed to examine the association between healthcare resources and heatwave-mortality risk. Findings: A total of 310,363 deaths were analyzed in 74 districts. The lag-cumulative heatwave-related mortality (RRs) ranged from 1.12 (95% confidence interval [CI]: 1.07, 1.17) to 1.21 (95% CI 1.05, 1.38), depending on the definitions used for heatwaves. Of the three PCs for healthcare resources (PC1: pre-hospital emergency medical service, PC2: hospital resources, PC3: timely access), timely access was associated with reduced risk of heatwave-related mortality, particularly among the elderly. Specifically, timely access to any emergency room (ER) exhibited the strongest association with lower heatwave-related mortality. Interpretation: Our findings suggest that timely access to any ER is more effective in reducing heatwave-related mortality risk than access to higher-level healthcare facilities, especially among the elderly. Therefore, healthcare resource factors and ER accessibility should be prioritized when identifying vulnerable populations for heatwaves, along with known individual and socio-demographic factors. Funding: This work was supported by the Research Program funded by the Korea Disease Control and Prevention Agency (2022-12-303), the National Research Foundation of Korea (NRF) grant funded by the Korean government (MSIT) (No. 2022R1A2C2092353) and the MD-PhD/Medical Scientist Training Program through the Korea Health Industry Development Institute (KHIDI), funded by the Ministry of Health & Welfare, Republic of Korea.